National Legal Frameworks for the Protection of Critical Digital Infrastructure in the Age of Global Cyber Threats - Dybio Asih; Jona Tarigan; Ririn Berutu (Sah Publisher, 2026)
The rapid escalation of global cyber threats has placed critical digital infrastructure at the center of national security concerns. Critical digital infrastructure - including financial systems, energy networks, telecommunications, healthcare platforms, and government information systems - has become increasingly vulnerable to sophisticated cyber attacks that transcend national borders. This study was undertaken to examine the adequacy of national legal frameworks in protecting critical digital infrastructure in the contemporary cyber threat environment. The research addresses a significant legal problem: the growing gap between the pace of technological advancement and the capacity of existing legal regimes to effectively prevent, mitigate, and respond to large-scale cyber threats. By building upon existing scholarship on cybersecurity law and critical infrastructure protection, this study seeks to provide a systematic legal analysis of national strategies and regulatory approaches in the digital era. This research employs a normative juridical method combined with a doctrinal legal analysis. Primary legal materials include national cybersecurity statutes, regulations on critical infrastructure protection, data protection laws, and relevant international legal instruments. Secondary materials consist of academic literature, policy reports, and comparative legal studies on cybersecurity governance. A comparative approach is used to examine selected national legal frameworks and identify common regulatory patterns, institutional arrangements, and enforcement mechanisms. The study also analyzes policy documents and official guidelines to assess how legal norms are translated into operational cybersecurity strategies. The findings indicate that while many states have adopted legal frameworks recognizing critical digital infrastructure as a strategic national asset, significant inconsistencies remain in regulatory scope, institutional coordination, and enforcement capacity. Most national frameworks emphasize preventive measures, such as risk assessment and incident reporting obligations, but lack comprehensive legal mechanisms for cross-sector coordination and international cooperation. The research confirms that existing laws partially address cybersecurity risks but are often reactive rather than anticipatory, limiting their effectiveness against rapidly evolving global cyber threats. The originality of this study lies in its integrated legal analysis of national cybersecurity frameworks through the lens of critical digital infrastructure protection. By linking legal norms, institutional design, and strategic objectives, the research contributes to a deeper understanding of how law can function as a proactive instrument of cyber resilience. The findings offer practical insights for policymakers and legal scholars and suggest future research directions, including the harmonization of national laws and the development of transnational legal mechanisms for critical infrastructure protection